Targeting efflux pumps prevents the multi-step evolution of high-level resistance to fluoroquinolone in Pseudomonas aeruginosa - Xiao-Quan Yu; Hao Yang; Han-Zhong Feng; Jun Hou; Jun-Qiang Tian; Shao-Min Niu; Chong-Ge You; Xuan-Yu Tao; Si-Ping Zhang; Zhi-Ping Wang; Yong-Xing He (Microbiology Spectrum)
ABSTRACT Antibiotic resistance is emerging as a significant global health crisis, necessitating the urgent development of novel antibiotics or alternative therapies. Although it is recognized that bacteria require multiple mutations to develop resistance levels exceeding the mutant prevention concentration, the specific mutation combinations conferring high resistance have been largely undefined. Here, we investigated the multi-step evolution of fluoroquinolone resistance in Pseudomonas aeruginosa through experimental evolution and whole-genome sequencing coupled with proteomic approaches. We discovered that in low-dose and high-dose experimental evolution scenarios, combinations of mutations in the negative regulators of efflux pumps (nfxB/mexR) and DNA gyrases (gyrA/gyrB) contributed to the high-level resistance and some of these combinations were also prevalent in clinical isolates of P. aeruginosa. Notably, the selected nfxB mutation, which resulted in the overexpression of the MexCD-OprJ efflux pump, also exhibited collateral sensitivity to aminoglycosides and enhanced antibiotic tolerance. It was further revealed that the efflux pump inhibitor phenylalanine-arginine β-naphthylamide (PAβN) could effectively prevent evolution to high-level resistance for both laboratory and clinical P. aeruginosa strains. Our work highlights the critical role of efflux pump repressor-related mutations in the evolution of high-level antibiotic resistance and demonstrates the potential of targeting these mutations to impede the evolution toward high-level resistance.IMPORTANCEIn this study, we examined the stepwise evolution of fluoroquinolone resistance in Pseudomonas aeruginosa using experimental evolution, whole-genome sequencing, and proteomic analyses. Our findings revealed that under both low-dose and high-dose conditions, mutations in efflux pump regulators (nfxB/mexR) and DNA gyrase genes (gyrA/gyrB) synergistically contributed to high-level resistance. These mutation combinations were not only observed in experimental settings but also detected in clinical isolates of P. aeruginosa. This work underscores the pivotal role of efflux pump repressor-related mutations in the progression to high-level antibiotic resistance. It also highlights the promise of targeting efflux pumps as a strategy to prevent the multi-step evolution of resistance in P. aeruginosa.